Butler Matrix Based Six-port Passive Junction - Moscoso Mártir, Álvaro; Ávila Ruiz, Juan Manuel; Durán Valdeiglesias, Elena; Moreno-Pozas, Laureano; Molina-Fernández, Íñigo; Ortega-Moñux, Alejandro; De-Oliva-Rubio, José (My University, 2014)
In this work we propose the utilization of the Butler matrix as a six-port I/Q demodulator. The inherent symmetry of its topology allows to overcome the intrinsic amplitude and phase imbalances of the traditional approaches making it more suitable for the design of high performance six-port networks. To demonstrate the validity of the proposal a Butler matrix has been designed covering the complete UWB band and its results are compared with the traditional approaches.